(untitled) (Eurasian Journal of Learning and Academic Teaching, 2026)
This article examines the scientific, theoretical, and methodological foundations for developing student competencies in data management through case study-based practical training in the context of digitalization in agriculture. It describes the stages of case study development, the practical training algorithm, assessment criteria, levels of competency development, and mechanisms for evaluating the results of experimental tests